2010
DOI: 10.1214/09-aop507
|View full text |Cite
|
Sign up to set email alerts
|

The obstacle problem for quasilinear stochastic PDE’s

Abstract: We prove an existence and uniqueness result for the obstacle problem of quasilinear parabolic stochastic PDEs. The method is based on the probabilistic interpretation of the solution by using the backward doubly stochastic differential equation.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 10 publications
3
54
0
Order By: Relevance
“…✷ Remark 4.7. In the particular case where L = ∂ ∂t + 1 2 ∆, f u ≡ 0, u is quasi-continuous and ϕ ≡ 0 results of Theorem 4.6 agree with those given in [24] (Theorem 2, Lemma 3), because the transition function p of the Wiener process is symmetric. For instance, integrating (4.8) with s = 0 with respect to m(dx) we get Theorem 3(v) in [24].…”
Section: Parabolic Potentials Soft Measures and Additive Functionalssupporting
confidence: 72%
See 2 more Smart Citations
“…✷ Remark 4.7. In the particular case where L = ∂ ∂t + 1 2 ∆, f u ≡ 0, u is quasi-continuous and ϕ ≡ 0 results of Theorem 4.6 agree with those given in [24] (Theorem 2, Lemma 3), because the transition function p of the Wiener process is symmetric. For instance, integrating (4.8) with s = 0 with respect to m(dx) we get Theorem 3(v) in [24].…”
Section: Parabolic Potentials Soft Measures and Additive Functionalssupporting
confidence: 72%
“…For instance, integrating (4.8) with s = 0 with respect to m(dx) we get Theorem 3(v) in [24]. Furthermore, taking expectation of (4.11) with s = 0, multiplying it by η ∈ L 2 (R d ) and then integrating with respect to m(dx) and using (4.8) we get Lemma 3 in [24]. We now recall the notion of soft measures (see [11]).…”
Section: Parabolic Potentials Soft Measures and Additive Functionalsmentioning
confidence: 98%
See 1 more Smart Citation
“…Forker (1992), for example, argued that that the separation of functions can increase the quality of control and reduce the probability of information retention of by leaders, which will substantially improve the quality of information disclosure. However, Hanifa and Cooke Finally, on a sample of 128 French companies belonging to the SBF250 index, Matoussi and Mahfoudh (2010) found that the separation between the functions of the chairman of the Board and those of the chief executive office compels the leader to engage in an "opportunistic" earnings management. This result is in line with the work carried out recently by Kantadu and Samaila (2015).…”
Section: The Combination or The Separation Of Functions And Earnings mentioning
confidence: 99%
“…More recently, Matoussi and Stoica [37] studied the obstacle problem for parabolic quasilinear SPDEs and gave a probabilistic interpretation of the reflected measure ν in terms of the associated increasing process which is a component of solution of reflected BSDEs. Such measures are called regular measures or Revuz measures.…”
Section: Introductionmentioning
confidence: 99%